RELATIONSHIP OF BILIARY TRACT DISEASES WITH SOME CHRONIC DISEASES AMONG THE RURAL POPULATION - Sadigov, I.A.; Gidayatov, A.A. (World of Medicine and Biology, 2012)
The purpose of research was to examine the relationship of chronic biliary tract disease, with some prevalent chronic diseases: hypertension (AH), diabetes mellitus (DM type II), peptic ulcer, 12 duodenal ulcer (DU), thyroid disease (TD), nephrolithiasis (NL). Carried out a survey two-staged examination of the Azerbaijan population living in villages of Marneuli region of Georgia. Prevalence of diseases of biliary tract are in close correlation with the epidemic rise of other "diseases of civilization" that occur with profound metabolic disorders: hypertension, thyroid disease, kidney disease and type 2 diabetes.
Keywords: chronic biliary tract disease; chronic disease; correlation